Factors which influence the consumption of street foods and fast foods in South Africa-a national survey - Steyn Nelia P (Nutrition Journal, 2011)
Abstract Background Very little is known about street food and fast food consumption patterns in South Africa despite this being a large sector of the national economy in terms of employment provided and sales of food. The objective of this study was to determine the use of street foods and fast foods purchased by South Africans living in different provinces and geographic areas. Methods A cross-sectional survey was conducted. Structured interview-administered questionnaires in 11 official languages were conducted at the participants' homes. A nationally representative sample (n = 3287) was drawn from all ethnic groups, and provinces including participants 16 years and older. Logistic regression was done to evaluate factors impacting on fast food consumption. Results Frequent (2 ≥ times/week) street food consumption ranged from 1.8% in Northern Cape to 20.6% in Limpopo; frequent (2 ≥ times/week) fast food consumption ranged between 1.5% in North West Province to 14.7% in Gauteng. The highest intake of street food was in the medium socio-economic category (14.7%) while the highest intake of fast foods was in the high socio-economic category (13.2%). Overall, fruit was the most commonly purchased street food by all ethnic groups over the previous week although this practice was highest in black participants (35.8%). Purchases of soft drinks ranged from 4.8% in whites to 16.4% in blacks and savoury snacks from 2.3% to 14.5% in whites and blacks, respectively. Consumption of fast foods and street foods were influenced by a number of socio-demographic factors including ownership of major home appliances. Frequent fast food consumers had a significantly higher dietary diversity score (4.69; p < 0.0001) while frequent street food consumers had a significantly lower score (3.81; p < 0.0001). Conclusions A large percentage of the population purchase street foods and fast foods. This is of some concern when one notes the high prevalence of soft drink consumption in terms of its association with obesity and non-communicable diseases. These findings need to be taken into consideration when evaluating dietary patterns and nutritional adequacy of population diets.